Residual modulation reduction in optical sectioning using a suitable spatial light modulator waveform - Han, Jeong-Heon; Yoo, Nak-Won; Kim, Myung-Ha; Ju, Byeong-Kwon; Park, Min-Chul (OPTICAL SOC AMER, 2019)
We propose a method to improve the axial response of structured illumination microscopy via selection of an illumination pattern with a sinusoidal or square wave within the cutoff frequency of the imaging system. Residual modulation within a sectioned image is mitigated by accurate phase-shifting via the electrical spatial light modulator control signal, which is based on an illumination pattern having a suitable waveform. Reduction in residual modulation is observed in the sinusoidal pattern with a spatial frequency sufficiently below the cutoff frequency of the imaging system. This reduction is larger for the square wave as the spatial frequency approaches one-third of the cutoff frequency. (C) 2019 Optical Society of America.
Keywords: STRUCTURED-LIGHT; MICROSCOPY; INSPECTION; SPEED; CELLS